A review on the approaches in analysing energy-related occupant behaviour research. (August 2021) - Tuniki, Himanshu Patel; Jurelionis, Andrius; Fokaides, Paris
Abstract: The effect of occupant behaviour on the energy performance of a building is one of the most important and critical parameters in building energy studies. Occupant behaviour, driven by dissatisfaction can lead to significant disconnect between the predicted and actual building energy performance. To monitor occupant behaviour as a variable in energy performance studies, it is imperative to select the appropriate method of data collection and interpretation. This paper investigates the research conducted on energy related occupant behaviour, which can be utilised for energy performance studies and simulations. Specifically, this review focuses on the findings of the works conducted post-2015 in separate sections within this paper and attempts to shed light on the various occupant behaviour analysis methods employed by the researchers, with the aim of transferring the data obtained into building energy performance simulations. An overview of selected studies is given in the form of a comprehensive review matrix, linking those with six different types of simulation methods, the different variables and the experimental investigations considered for the study. Highlights: About 150 articles have been studied for the review. 70 articles selected through the Review Matrix are reviewed in detail. The Pre-/Post-Occupancy method is determined to include more variables in a study. 90% of the studies were focused on thermal comfort and 78% have used sensors. 67% of the studies have used surveys and 68% have included simulation tools.